A Down Draft Gasifier of Biomass Gasification - Khatri, Pawan Kumar (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Great environmental concern is expressed over the release of CO2 from the burning of fossil fuels. When fossil fuels are burnt, carbon from fuels reacts with oxygen from air and produce CO2. This is the reason for steady increasing CO2 content of atmosphere. Carbon dioxide contributes to 50% of green house effect. There is a need to balance the increasing demands for the electricity while simultaneously avoiding the adverse impacts on the environment. Nowadays, other field of research is the production of hydrogen as a fuel from the gasification process of different types of biomass.it is the simplest and economical process to produce thermal energy. How to cite this article: Khatri PK. A Down Draft Gasifier of Biomass Gasification. J Adv Res Alt Energ Env Eco 2018; 5(1&2): 25-28.